Comparison of Disease Progression in Patients with Osteoarthritis of Knee Treated with Versus without Intraarticular Injection of Corticosteroids - Rehman, Saif ur; Afzal, Tanveer; Iqbal, Safdar; Haq, Abrar-Ul-; Abidin, Muhammad Zain-Ul-; Aslam, Farhan (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To compare the frequency of disease progression in patients with osteoarthritis of knee treated with versus without intra-articular injection of corticosteroids. Design: The present study was a randomized single-blind controlled trial. Study Settings: The current study was conducted at Department of Orthopedic Surgery at Sir Ganga Ram Hospital Lahore over 1 year from May 2020 to April 2021. Study Procedure: The present study was conducted over 186 patients of both genders aged between 40-70 years presenting in outpatient department of orthopedic surgery with osteoarthritis of knee joint. The sampled patients were randomly allotted into two treatment arms. Patients from Group-A received intraarticular injection of steroids in addition to conservative management while those in Group-B were taken as controls and were managed conservatively without intraarticular injection of steroids. Outcome variable was frequency of disease progression over KL grading which was noted and compared between the groups. An informed on paper consent was obtained from every participant. Results: The mean age of the patients was 52.5±8.7 years. There was a female predominance with a male to female ratio of 1:1.7. The mean BMI of these patients was 28.3±3.6 Kg/m2 and 60 (32.3%) patients were obese. 103 (55.4%) patients had grade 2 while 83 (44.6%) patients had grade 3 osteoarthritis. Disease progression was noted in 30 (16.1%) patients after 6 months follow-up. The frequency of disease progression was significantly higher in patients receiving intra-articular injection of corticosteroids as compared to controls (26.9% vs. 5.4%; p-value<0.001). When stratified, comparable difference was observed across various subgroups of patients based on patient’s age, gender, BMI and baseline Kellgren-Lawrence Grade. Conclusion: In the present study intraarticular injection of steroids was found to be associated with articular cartilage damage evident from increased frequency of disease progression following intraarticular injection as compared to controls which advocates that intraarticular injection of steroids should be avoided in the management of osteoarthritis and should be reserved only for patients with advanced disease and who are already planned for joint replacement.